2012
DOI: 10.1103/physrevb.85.064402
|View full text |Cite
|
Sign up to set email alerts
|

Al doping effect on magnetic phase transitions of magnetoelectric hexaferrite Ba0.7Sr1.3Zn2

Abstract: We investigated the effect of Al doping in magnetic properties of the Y-type hexaferrite Ba 0.7 Sr 1.3 Zn 2 (Fe 1−x Al x) 12 O 22 (0 x 0.12), which exhibit field-induced magnetoelectric polarization. We find that Al doping increases the pitch of a spin helix and enhances c-axis magnetization, stabilizing longitudinal conical phases. These conical phases eventually collapse at x 0.10. These results suggest that competitions between easy-axis and easy-plane anisotropy fields play a key role in generating stable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 37 publications
(77 reference statements)
1
26
0
Order By: Relevance
“…As we known, two coexisting magnetic anisotropy fields, easy axis, and easy plane with respect to the c axis of the hexagonal lattice, are responsible for the heliconical order in Y-type hexaferrites. 18 For Co 2 Y hexaferrites, Co 2+ ions can contribute to additional anisotropy terms, 19,21 which makes the spin more difficult to rotate during magnetization reversal. Therefore, at low temperatures, most of the transverse conical can be maintained at zero field, leading to an irreversible M-H curve.…”
Section: August 2015mentioning
confidence: 99%
See 1 more Smart Citation
“…As we known, two coexisting magnetic anisotropy fields, easy axis, and easy plane with respect to the c axis of the hexagonal lattice, are responsible for the heliconical order in Y-type hexaferrites. 18 For Co 2 Y hexaferrites, Co 2+ ions can contribute to additional anisotropy terms, 19,21 which makes the spin more difficult to rotate during magnetization reversal. Therefore, at low temperatures, most of the transverse conical can be maintained at zero field, leading to an irreversible M-H curve.…”
Section: August 2015mentioning
confidence: 99%
“…11,16 Chun et al 17 reported that the nonmagnetic Al 3+ ion replacement of the magnetic Fe 3+ ion can induce a giant ME susceptibility of 2.0 9 10 4 ps/m in Ba 0.5 Sr 1.5 Zn 2 (Fe 1Àx Al x ) 12 O 22 (Zn 2 Y) at x = 0.08 and 30 K. The improvement of its magnetoelectric properties was interpreted by the fact that Al-substitution can stabilize the longitudinal conical phase, which can turn into transverse conical structure by applying a low magnetic field. 18 In this work, we investigate the field-induced ME effect of Al-substituted Co 2 Y type Ba 0.5 Sr 1.5 Co 2 (Fe 1Àx Al x ) 12 O 22 hexaferrites. Co 2+ ions, different from Zn 2+ ions, are magnetic and they can contribute to the enhancement of the magnetic ordering temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it is proposed that Al doping suppresses magnetic anisotropy, and the reduction of magnetic anisotropy is plausibly the origin of the conical magnetic structures in BSZFAO. 13,16 Figure 4 shows the temperature dependence of the peak 1 frequency for BSZFO and BSZFAO in a zero magnetic field. The Bloch T 3/2 law fits well for both BSZFO and BSZFAO, meaning that the low-temperature excitation is gapless spin wave in ferromagnetic phase.…”
Section: Resultsmentioning
confidence: 99%
“…The different magnetic structures change from planar helix to collinear ferrimagnetic ordering, with several intermediate commensurate magnetic spin phases with mixed conical structure, called I, II and III (the spin orientations in this phases can be seen in [4,8,19]). For each composition, some of the above, as well as alternate longitudinal conical (ALC) and transverse conical (TC) can take place at different values of temperature and applied magnetic field leading to a complex magnetic phase diagram [4,8,35,36]. Unless the spin induced ferroelectric order is usually attributed to the TC spiral system, other authors have suggested that the intermediate II and III spin systems can also promote electric polarization [1,4,37].…”
Section: Discussionmentioning
confidence: 99%